BKCa and hEag1 Channels Regulate Cell Proliferation and Differentiation in Human Bone Marrow‐Derived Mesenchymal Stem Cells. Issue 2 (25th October 2013) - Zhang, Ying‐Ying; Yue, Jianbo; Che, Hui; Sun, Hai‐Ying; Tse, Hung‐Fat; Li, Gui‐Rong
<x xml:space="preserve">Abstract</x> Human bone marrow‐derived mesenchymal stem cells (MSCs) serve as a reservoir for the continuous renewal of various mesenchymal tissues; however, cellular physiology of ion channels is not fully understood. The present study investigated potential roles of large‐conductance Ca2+‐activated potassium (BKCa) channels and ether‐à‐go‐go potassium (hEag1 or Kv10.1) channels in regulating cell proliferation and differentiation in human MSCs. We found that inhibition of BKCa with paxilline or hEag1 with astemizole, or knockdown of BKCa with shRNAs targeting KCa1.1 or hEag1 channels with shRNAs targeting KCNH1 arrested the cells at G0/G1 phase. In addition, silencing BKCa or hEag1 channels significantly reduced adipogenic differentiation with decrease of lipid accumulation and expression of the adipocyte marker PPARγ, and decreased osteogenic differentiation with reduction of mineral precipitation and osteocalcin. These effects were accompanied with a reduced cyclin D1, cyclin E, p‐ERK1/2, and p‐Akt. Our results demonstrate that BKCa and hEag1 channels not only regulate cell proliferation, but also participate in the adipogenic and osteogenic differentiations in human MSCs, which indicates that BKCa and hEag1 channels may be essential in maintaining bone marrow physiological function and bone regeneration. J. Cell. Physiol. 229: 202–212, 2014. © 2013 Wiley Periodicals, Inc.